Tindak Pidana Pencurian Getah Karet oleh Anak di Wilayah Hukum Polsek Tebo Ulu dalam Analisis Kriminologis - Hartono, M. Rudi; Aditama, Ryan; Saumia, Asmi (Universitas Batanghari Jambi, 2023)
In criminology, many theories have developed to examine why someone commits a crime, while generally other people do not. In principle, these theories conclude that a person's crime can originate from within the person, both physically and psychologically, or the crime can originate from outside the person, in this case crime is considered to originate from the behavior patterns of the community around the person's life. this, as well as because of the inequality in society's economic system. Criminals (criminals) are the subject of criminology. Understanding what drives a person to commit a crime or crime is the goal of criminology. Is this person's propensity to commit crime since childhood truly a skill, or is it more likely the result of the sociological and economic circumstances of the surrounding environment. Therefore, it is vital to understand the motivation behind the crime and seek causes and solutions during the sentencing process to prevent repeat offenses. This research expects to get a more top to bottom picture of the business as usual of criminal demonstrations of robbery of elastic by youngsters in the Tebo Ulu Police Lawful Region, what variables cause criminal demonstrations of burglary of elastic by kids in the Legitimate Region of the Tebo Ulu Police, and endeavors to defeat them. in the wrongdoing of robbery of elastic plastic by kids in the Tebo Ulu Police Lawful Region. The technique utilized in this exploration is an exact examination strategy with a contextual analysis kind of exploration. The information assortment strategy in this examination utilized interviews. The finish of this examination is that criminal demonstrations of burglary by youngsters in the ward of the Tebo Ulu Police are impacted by a few elements including: absence of parental management, ecological factors and absence of instruction. Then, at that point, the Tebo Ulu Cops put forth attempts to handle the wild demonstrations of robbery committed by kids via completing preventive and abusive endeavors.